TEACHER’S STRATEGY IN IMPROVING STUDENT VOCABULARY MASTERY AT MTS MARDHATILLAH HIDAYATULLAH PALEMBANG - Eliza, Tiara; Berliani, Wulandari (Enrich: Jurnal Pendidikan, Bahasa, Sastra dan Linguistik, 2023)
Learning English vocabulary is essential for the improvement of students' language ability. Students should learn as much vocabulary as possible to establish good communication with other students. This study aims to investigate teacher’s strategy in improving student vocabulary mastery at MTs Mardhatillah Palembang as one of learning strategies outside of class activities. This study uses descriptive qualitative research where the researcher implements interview and observation as data collection techniques. The researcher used observation to understand the school environment where students learn English. To find out the student vocabulary mastery as learning strategies which is used by the teacher, the researcher used semi-structured interviews with the teachers and students as participants. The results showed that students most often used meta-cognitive strategies to improve their English vocabulary.